Pharmacist-Led Implementation of Brief Tobacco Cessation Interventions during Mobile Health Access Events - Karen Suchanek Hudmon; Julia S. Czarnik; Alexa M. Lahey; Susie J. Crowe; Megan Conklin; Robin L. Corelli; Jasmine D. Gonzalvo; Katy Ellis Hilts (Pharmacy, 2023)
To address gaps in care for individuals from under-resourced communities disproportionately affected by tobacco use, this pharmacist-led demonstration project evaluated the feasibility of implementing tobacco use screening and brief cessation interventions during mobile health access events. A brief tobacco use survey was administered verbally during events at two food pantries and one homeless shelter in Indiana to assess the interest and potential demand for tobacco cessation assistance. Individuals currently using tobacco were advised to quit, assessed for their readiness to quit, and, if interested, offered a tobacco quitline card. Data were logged prospectively, analyzed using descriptive statistics, and group differences were assessed by site type (pantry versus shelter). Across 11 events (7 at food pantries and 4 at the homeless shelter), 639 individuals were assessed for tobacco use (n = 552 at food pantries; n = 87 at the homeless shelter). Among these, 189 self-reported current use (29.6%); 23.7% at food pantries, and 66.7% at the homeless shelter (p < 0.0001). About half indicated readiness to quit within 2 months; of these, 9 out of 10 accepted a tobacco quitline card. The results suggest that pharmacist-led health events at sites serving populations that are under-resourced afford unique opportunities to interface with and provide brief interventions for people who use tobacco.